Investigation of Kurdish students’ L2 motivational self-system and their motivational beliefs in high school - Abdullah, Kameran Noori; Razi, Özge (Frontiers in Psychology, 2022)
This study aims to examine and compare female and male Kurdish EFL students’ level and type of motivation based on L2 motivational self-system components and to identify their dominant type of motivation. The participants of this study were 118 students (46 female, and 72 male) were randomly selected as the participants of this study from different cities of Erbil governorate in Kurdistan region of Iraq. A Learners questionnaire that was originally developed by Dornyei et al. (2006), whose reliability and validity had been approved, used following the application of semi-structured interview sessions with learners who participated in the study. The data obtained from the questionnaire were analyzed through SPSS software, and the interview results were interpreted and analyzed through content analysis. The findings of this study revealed that both male and female Kurdish EFL students generally have high levels of motivation and the attitudes of both groups of learners were found to be generally positive towards English language and its learning. The most frequent motivational strategies, ways of motivating and arranging for them a suitable culture and recommended by the teachers in this study are helpful, especially for teacher educators in teacher training programs, so that they can get aware of the most used strategies by Kurdish EFL teachers in high school to be the leadership for this purpose, and try to improve and correct them, and try to teach them the most effective strategies and ways of raising motivation in the students.